Early Adolescent’s Conservation of Internal Volume - PACHAURY, A.C. (SCHOOL SCIENCE, 2007)
PIAGET AND HIS collaborators had used conservation of volume to judge Genevan children’s level of cognitive development. Their studies have demonstrated that conservation of volume is attained in three sequential phases of 8-years (internal volume); 9- years (liquid volume) and 11/12-years (occupied/displaced volume). Piagetians had fixed 75% level of performance as an index of conservation attainment by the target group. Researches conducted on early adolescents’ (11/12-year) occupied/ displaced volume tasks show 25 to 48% level of performances (Beard; Elkind; Lovell; Uzgiris; Vernon; VinhBang and Inhelder, all cited in Fogelman, 1970). Conservation of internal volume has been spurtly studied here as well as abroad.